SYNONYMIC AND ANTONYMIC FEATURES OF CONFECTIONERY NAMES IN ENGLISH AND UZBEK LANGUAGES - Farida Normurotovna Safarova (Scholars Digest Publishing, 2023)
This article is dedicated to the synonymic and antonymic features of English and Uzbek languages. Also, confectionary names are studied in comparison.
Keywords: synonyms, explanation, lexeme, antonyms, confectionary, features, determined, dedicated, compared.